2016
DOI: 10.1007/s11696-016-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a new gel polymer electrolyte containing core–shell silica–polyelectrolyte nanoparticles via activators regenerated by electron transfer atom transfer radical polymerization (ARGET-ATRP) for high-performance lithium–sulfur batteries

Abstract: Presented herein is the fabrication of a new gel polymer electrolyte (GPE) containing core-shell nanoparticles for lithium-sulfur (Li-S) batteries. This work is to overcome drawbacks of poly (vinylidenefluoride) (PVDF)-based GPEs while simultaneously maintaining their beneficial electrochemical properties such as high ionic conductivity at ambient temperature and excellent chemical stability. Core-shell silica nanoparticles with silica as core and poly (vinylbenzenesulfonate) as shell was synthesized via activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…As for the preparation strategy of GPEs, it generally includes three steps: (a) Synthesizing polymer hosts; (b) obtaining membrane-like polymer hosts via solution-casting [43,44], electrospun [45][46][47], phase inversion [48,49] or hot-pressing [50]; and (c) immersing the membrane into liquid solutions containing lithium salts. In the preparation process of GPEs, solid hosts can be swelled in two ways: the polyporous crosslinking network and the partial gelation of hosts [20,51,52].…”
Section: Gel Polymer Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the preparation strategy of GPEs, it generally includes three steps: (a) Synthesizing polymer hosts; (b) obtaining membrane-like polymer hosts via solution-casting [43,44], electrospun [45][46][47], phase inversion [48,49] or hot-pressing [50]; and (c) immersing the membrane into liquid solutions containing lithium salts. In the preparation process of GPEs, solid hosts can be swelled in two ways: the polyporous crosslinking network and the partial gelation of hosts [20,51,52].…”
Section: Gel Polymer Electrolytesmentioning
confidence: 99%
“…To further improve long-term cycling performance of cells, SiO 2 with novel structure has been recently designed. For instance, Sovizi et al [49] fabricated novel type SiO 2 nanoparticles with core (SiO 2 )shell (poly(vinylbenzenesulfonate)) structure for PVdF-based Li-S batteries. Compared with the no fillers added electrolytes, the obtained CGPE improved discharge capacity from 350 mAh g À1 to 400 mAh g À1 after 100 circles at 0.2C.…”
Section: Fillers Added Into Gpesmentioning
confidence: 99%
“…Similarly, Ji and coworkers [104] demonstrated that Si-O groups on surface of silica nanoparticles can entrap polysulfide through supramolecular interactions. For one study, Madram et al [105] firstly synthesized core-shell Si nanoparticles by grafting shell of poly(vinylbenzenesulfonate) on the surface of Si core, and then prepared GPEs by mixing PVDF with core-shell Si nanoparticles, as is shown in Fig. 9(b).…”
Section: Polymer With Vdf Based Gpesmentioning
confidence: 99%